Gamified human resource management as a driver of employee engagement through intrinsic motivation - Zhang, Xuming; Wang, Jinliang; Zhu, Yiming; Ding, Zhaoqiao (Frontiers in Psychology, 2026)
In the digital transformation era, maintaining employee work engagement has become a persistent challenge, as traditional incentive systems often fail to satisfy younger employees’ psychological needs for autonomy, competence, and relatedness. Gamified Human Resource Management (HRM) offers a novel means of enhancing work engagement through game-based mechanisms, yet prior studies have largely overlooked the mediating role of intrinsic motivation and the contextual contingencies shaping its effects. Drawing on self-determination theory (SDT), this study develops and empirically tests an integrated model using survey data collected from 418 respondents. The results of structural equation modeling reveal that gamified HRM significantly enhances work engagement, with intrinsic motivation partially mediating this relationship. Moreover, gaming preference and perceived organizational support moderate the positive effect of gamified HRM on engagement. These findings extend SDT by clarifying how gamified HR practices fulfill basic psychological needs and underscore that their effectiveness depends on the alignment between individual dispositions and organizational climate.